2020
DOI: 10.1038/s41440-020-0469-2
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and v1br gene expression is increased in the hypothalamic pvn of borderline hypertensive rats

Abstract: Vasopressin (VP) is a neurohypophyseal peptide best known for its role in maintaining osmotic and cardiovascular homeostasis. The main sources of VP are the supraoptic and paraventricular (PVN) nuclei of the hypothalamus, which co-express the vasopressin V1a and V1b receptors (V1aR and V1bR). Here we investigate the level of expression of VP and VP receptors in the PVN of borderline hypertensive rats (BHRs), a key integrative nucleus in neuroendocrine cardiovascular control. Experiments were performed in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…In these rats no changes in VP and VR gene transcription in the PVN was noted. Moreover, systemic VP release was decreased, refuting involvement of VP in stress-induced hypertension ( Savić et al, 2020 ).…”
Section: Paraventricular Nucleus and Blood Pressure Short-term Variab...mentioning
confidence: 94%
See 2 more Smart Citations
“…In these rats no changes in VP and VR gene transcription in the PVN was noted. Moreover, systemic VP release was decreased, refuting involvement of VP in stress-induced hypertension ( Savić et al, 2020 ).…”
Section: Paraventricular Nucleus and Blood Pressure Short-term Variab...mentioning
confidence: 94%
“…We have investigated the neurochemical contribution of the PVN to short-term BPV, and found that both VP and OT modulate short-term BPV. Using pharmacological and genetic tools in conscious rats we have shown that VP modulates BPV in a complex manner: peripherally as a hormone and centrally as neurotransmitter/modulator ( Japundzic-Zigon, 2001 , 2013 ; Japundzić-Zigon et al, 2004 , 2018 , 2020 ; Milutinović et al, 2006a , b ; Stojicić et al, 2008 ; Milutinović-Smiljanić et al, 2013 ; Lozić et al, 2016 ; Savić et al, 2020 ). Using spectral analysis of BPV, we found that peripheral administration of non-peptide and selective V1aR or V2R antagonists to conscious normotensive rats under baseline physiological conditions increases BPV, suggesting a buffering role for VP in the VLF domain ( Japundzic-Zigon, 2001 ).…”
Section: Paraventricular Nucleus and Blood Pressure Short-term Variab...mentioning
confidence: 99%
See 1 more Smart Citation
“…It seems that in BHRs, an elevated level of circulating plasma noradrenaline changes vascular reactivity and contributes to differential haemodynamic adaptations (Fuchs et al., 1998 ). The BHRs are characterized by a high plasma concentration of vasopressin (Savic et al., 2020 ), and exogenous vasopressin provoked pressor‐induced cardiac hypertrophy (Fuchs et al., 1998 ). Furthermore, crowding stress elevates plasma corticosterone and accelerates development of hypertension in juvenile male (Bernatova et al., 2018 ) and female BHRs (Slezak et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Signals from the radiotelemetry devices were transmitted to a data acquisition and analysis system composed of a Data Exchange arterial blood pressures and the pulse interval (PI) or its inverse value, heart rate (HR), were derived from the arterial PP wave as the maximum, minimum and interbeat interval, respectively. The signal length used for analysis was 409.6 s (Savic et al, 2020).…”
Section: Cardiovascular Signal Processing and Analysismentioning
confidence: 99%